Pacing in lane-based head-to-head competitions: A systematic review on swimming - Menting, S. G. P.; Elferink-Gemser, M. T.; Huijgen, B. C.; Hettinga, F. J. (Journal of Sports Sciences, 2019)
Athletes` energy distribution over a race (e.g. pacing behaviour) varies across different sports. Swimming is a head-to-head sport with unique characteristics, such as propulsion through water, a multitude of swimming stroke types and lane-based racing. The aim of this paper was to review the existing literature on pacing behaviour in swimming. According to PRISMA guidelines, 279 articles were extracted using the PubMed and Web of Science databases. After the exclusion process was conducted, 16 studies remained. The findings of these studies indicate that pacing behaviour is influenced by the race distance and stroke type. Pacing behaviours in swimming and time-trial sports share numerous common characteristics. This commonality can most likely be attributed to the lane-based racing set-up. The low efficiency of swimming resulting from propulsion through the water induces a rapid accumulation of blood lactate, prompting a change in swimmers` biomechanical characteristics, with the goal of minimising changes in velocity throughout the race. Although the literature on youth swimmers is scarce, youth swimmers demonstrate more variable pacing profiles and have more difficulty in selecting the most beneficial energy distribution.